1997
DOI: 10.1099/0022-1317-78-9-2191
|View full text |Cite
|
Sign up to set email alerts
|

Marek's disease virus EcoRI-Q gene (meq) and a small RNA antisense to ICP4 are abundantly expressed in CD4+ cells and cells carrying a novel lymphoid marker, AV37, in Marek's disease lymphomas.

Abstract: Mature lymphomas produced in Rhode Island

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 33 publications
1
41
0
Order By: Relevance
“…The Meq protein is a transactivating bZIP protein homologous to fos and jun oncogene products, and has an anti-apoptotic activity [12,14,15]. The Meq protein is consistently expressed in the vast majority of MD-transformed cell lines and CD4+ T cells obtained from lymphomas [24]. Oligonucleotides and RNA complementary to the meq gene can prevent the growth of MDV cell lines [29], and overexpression of Meq in rat-2 fibroblasts by recombinant murine retrovirus leads to transformation of the cells [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…The Meq protein is a transactivating bZIP protein homologous to fos and jun oncogene products, and has an anti-apoptotic activity [12,14,15]. The Meq protein is consistently expressed in the vast majority of MD-transformed cell lines and CD4+ T cells obtained from lymphomas [24]. Oligonucleotides and RNA complementary to the meq gene can prevent the growth of MDV cell lines [29], and overexpression of Meq in rat-2 fibroblasts by recombinant murine retrovirus leads to transformation of the cells [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…The meq antigen has been reported to be expressed in a variable proportion of MDV-transformed lymphoblasts in both cell lines and natural tumors. 31 The CD4ϩ CD8Ϫ lymphoblast is a principal target cell population for MDV transformation. 32 The present results suggest that late proliferative lesions in the CNS contain at least some MDV-transformed cells.…”
Section: Discussionmentioning
confidence: 99%
“…after MDV infection, and AV37 was thought to perhaps be associated with MHC class I and II expression, thus suggesting a possible role in activation of the cells. Ross et al (1997) found that expression of AV37 in CD4 + cells correlated with expression of a putative MDV oncogene, meq, (Jones et al, 1992) and small RNAs antisense to ICP4 (SAR) (Li et al, 1994;Xie et al, 1996;Cantello et al, 1997). T-cells do not enjoy an invariable monopoly on susceptibility to transformation since both B-and T-cell lymphoblastoid cell lines have been derived from MDV-induced lymphomas from turkeys (Nazerian & Sharma, 1985;Powell et al, 1984).…”
Section: Target Cellsmentioning
confidence: 99%
“…They include: a 1.8-kb family of RNAs which are present in oncogenic viruses, but are truncated in attenuated MDV variants (Maotani et al, 1986;Bradley et al, 1989;Peng et al, 1992); a 38-kDa phosphoprotein (pp38) found in cell lines and tumour cells (Cui-ef al, 1990); the MDV ICP4 homologue (Anderson et al, 1992), and a group of latency-related RNAs which map antisense to the ICP4 gene and are found in MD lymphoblastoid cell lines and in productively infected chicken embryo fibroblasts (Li et al, 1994;McKie et al, 1995;Cantello et al, 1997); a basic-leucine zipper gene, meq, which is expressed in all MD cell lines and MDV-induced tumours (Jones et al, 1992); and AV37 (Burgess et al, 1996;Kaiser et al, 1996;Ross et al, 1996Ross et al, , 1997, a novel antigen found on infected and transformed cells. The evidence that these various candidate genes and proteins are involved in oncogenesis with MDV is incomplete and, in some cases, very tenuous or completely absent.…”
Section: Differing Rates Of Integration Of Viral Dnamentioning
confidence: 99%
See 1 more Smart Citation